PENERAPAN WARNA LAMPU TUBE LUMINESCENT DALAM MENENTUKAN EMOSI TOKOH PADA FILM LOVE FOR SALE 2 - Hendra Fitriyanto Harahap; Sapto - Hudoyo (Texture: Visual Art and Culture Journal, 2023)
Fictional films are entertainment media created by a group of filmmakers and presented to the audience with stories and audio-visual techniques. Qualitative descriptive research, a research process that tries to get descriptive speech or writing. The use of luminescent tube lights in the film Love for Sale 2 has meaning in every scene.The color of the luminescent tube lights cannot be placed in just any place because the location of the luminescent tube lights can represent the emotions of each character, such as when Ican and Poppy first dated, the luminescent tube lights differentiated the emotion between the blue neon around Poppy which meant Poppy has cold emotions while orange is on the side of Ican, who is Poppy’s opponent, who has warm emotions, a dispute between Ros’ neighbors and Ros, whose red luminescent tube lamp is in the middle of them.